Formation and fate of oil-related aggregates (ORAs) in seawater at different temperatures. (October 2020) - Henry, Ingrid A.; Netzer, Roman; Davies, Emlyn J.; Brakstad, Odd Gunnar
Abstract: In this study, the formation and fate of oil-related aggregates (ORAs) from chemically dispersed oil in seawater (SW) were investigated at different temperatures (5 °C, 13 °C, 20 °C). Experiments in natural SW alone, and in SW amended with typical marine snow constituents (phytoplankton and mineral particles), showed that the presence of algae stimulated the formation of large ORAs, while high SW temperature resulted in faster aggregate formation. The ORAs formed at 5 °C and 13 °C required mineral particles for sinking, while the aggregates also sank in the absence of mineral particles at 20°. Early in the experimental periods, oil compound accumulation in ORAs was faster than biodegradation, particularly in aggregates with algae, followed by rapid biodegradation. High abundances of bacteria associated with hydrocarbon biodegradation were determined in the ORAs, together with algae-associated bacteria, while clustering analyses showed separation between bacterial communities in experiments with oil alone and oil with algae/mineral particles. Highlights: Oil-related marine snow was generated from chemically dispersed oil. Formation of aggregates was faster in seawater at high than at low temperatures. Aggregate sizes were larger in the presence than the absence of algae. Sinking oil-related aggregates were only observed at high seawater temperature. Oil compound groups were biodegraded in the aggregates. High abundances of oil-degrading bacteria were associated with the aggregates.